2016
DOI: 10.1586/17476348.2016.1164041
|View full text |Cite
|
Sign up to set email alerts
|

Is a pulmonary rehabilitation program effective in COPD patients with chronic hypercapnic failure?

Abstract: Given the significant reductions in pCO2 levels and significant increases in exercise capacity and QoL parameters after PR, the patients with chronic hypercapnic failure apparently benefited from the PR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
5
15
0
Order By: Relevance
“…In a study comparing hypercapnic and normocapnic COPD patients, the six-minute walk distance was found to be shorter in hypercapnic patients (39). In the present study, six-minute walk distance showed positive correlations with arterial saturation and PaO 2 but showed a negative correlation with PaCO 2 .…”
Section: Discussionsupporting
confidence: 51%
“…In a study comparing hypercapnic and normocapnic COPD patients, the six-minute walk distance was found to be shorter in hypercapnic patients (39). In the present study, six-minute walk distance showed positive correlations with arterial saturation and PaO 2 but showed a negative correlation with PaCO 2 .…”
Section: Discussionsupporting
confidence: 51%
“…For this reason, PR is considered to be one of the most efficient nonpharmacological methods in the treatment of COPD patients (24). Changes in pulmonary functions after PR show variation, however, and there are studies reporting no change in pulmonary functions (25,26) as well as the studies reporting increased FEV 1 values after PR (27)(28)(29). In our study, there was a significant increase in FEV 1 values in the normal-weight and pre-obese patients, whereas the increase in obese patients was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies demonstrated increased exercise capacity after PR (27)(28)(29). One study, which evaluated exercise capacity using an incremental shuttle walk test and endurance shuttle walk test by grouping the patients according to BMI found that the baseline ISWT value was significantly lower in obese patients and that there was a significant increase in all groups after PR, but the difference between the groups was not significant (31).…”
Section: Discussionmentioning
confidence: 99%
“…Even patients with chronic hypercapnic failure show benefit. 210 Limited data exist regarding the effectiveness of pulmonary rehabilitation after an acute exacerbation of COPD, but systematic reviews have shown that among those patients who have had a recent exacerbation (≤ 4 weeks from prior hospitalization), pulmonary rehabilitation can reduce…”
Section: Pulmonary Rehabilitationmentioning
confidence: 99%